OS AGENTES PENITENCIÁRIOS DE UM PRESIDIO DA REGIÃONOROESTE/RS E O ESTRESSE NO AMBIENTE DE TRABALHO - STUMM, ENIVA M. F.; WESCHENFELDER, MARLISE; POST, SANDRO D.; SINEMMANN, ANDRÉIA (Salão do Conhecimento, 2013)
Resumo